Sleep Quality and the Depression-Anxiety-Stress State of Frontline Nurses Who Perform Nucleic Acid Sample Collection During COVID-19: A Cross-Sectional Study - Chen X (Dove Medical Press, 2021)
Xiang Chen,* Ping Liu,* Guang-Feng Lei, Li Tong, Hui Wang, Xue-Qing Zhang Department of Nursing, The First People’s Hospital of Changde City, Changde, 415000, Hunan Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xue-Qing ZhangDepartment of Nursing, The First People’s Hospital of Changde City, 818 Renmin Road, Changde, 415000, Hunan Province, People’s Republic of ChinaEmail 382731326@qq.comObjective: To explore the sleep quality and depression-anxiety-stress state of frontline nurses in high-risk areas who conduct nucleic acid sampling testing for COVID-19 to provide a basis for formulating intervention programs in crisis management.Methods: From August 22 to 30, 2021, a convenient sampling method was used in Zhangjiajie City, Hunan Province, China. A total of 248 frontline nurses who performed nucleic acid sample collection were selected. The following tests were used: the general information questionnaire, Pittsburgh Sleep Quality Questionnaire (PSQI), and Depression–Anxiety Stress Scale (DASS-21).Results: A total of 236 nurses completed the survey; 88.14% (n = 208) were women, the average age was 33.02± 6.81, the PSQI score was 15 (13– 17), and 231 (97.88%) nurses had sleep disorders during the period in Zhangjiajie, 219 nurses (81.36%) had anxiety, 135 nurses (45.76%) had depression, and 112 nurses (42.59%) felt stressed. Spearman correlation analysis was used to associate the PSQI with the DASS-21. The results showed that the use of hypnotic drugs was negatively correlated with DASS-21 (P< 0.05), while the rest were positively correlated. The results of the multivariate analysis of sleep disorders showed that depression, anxiety, and stress were related to sleep quality (P< 0.05), and there was no statistical difference in the other variables.Conclusion: During the COVID-19 pandemic, the sleep quality and depression-anxiety-stress state of the frontline nurses performing nucleic acid testing were adversely affected. Sleep disturbance is a serious problem among nurses testing for the delta strain during the pandemic. Anxiety, stress, and depression are associated with sleep disorders. It is necessary to take corresponding measures and conduct crisis management interventions to improve sleep quality and mental health adjustment during public health emergencies.Keywords: COVID-19, perform nucleic acid sample collection, sleep quality, depression-anxiety-stress